Parents Knowledge about Early Childhood Sexual Education Based on Level of Education in Krasak Village, Pecangaan Sub-district, Jepara District - Faizah, Umi; Latiana, Lita (BELIA: Early Childhood Education Papers, 2017)
The high number of cases of child sexual abuse committed by the nearest children including the family shows the importance of early child sex education. Parents as educators in the family must have knowledge about sexual education for children. This study aims to find out whether there are differences in parental knowledge about early childhood sexual education based on education level in Krasak Village, Pecangaan Sub-district, Jepara Regency and whether parents graduate from Higher Education have knowledge about early child sexual education higher than parent who graduated High school and junior high school. This research type is quantitative with sample of parents who have children aged 4-6 years in Krasak Village, Pecangaan Sub-district, Jepara Regency. Data collection in this research is by using Parents Knowledge Scale of Early Childhood Sexual Education. Method of data analysis in this research is by using F test. The results of the study based on the calculation of statistical values ​​obtained F arithmetic> F table and Pvalue <0.05. Mean value in the group of parents who graduated from junior high school equal to 85.3, for the group of parents who graduated from high school 103.2, for the group of parents who graduated from college of 123.2. The result of research stated that there are differences of knowledge of parents who graduated from college based on education level and parents who graduated from higher education have higher knowledge than parents who graduated from high school.